2019
DOI: 10.1055/a-0851-9063
|View full text |Cite
|
Sign up to set email alerts
|

Multimodale Kommunikation in frühen Buchlesesituationen und ihr Zusammenhang mit dem späteren Wortschatz

Abstract: Early parent-child interactions are characterized by repeated communicative situations such as joint book reading. In these interactions, both interaction partners communicate using verbal, but also nonverbal means such as gestures. Nonverbal means enable children from early on to take an active part in communication. In our study, we observed 17 mothers and their 14-month-old children in naturalistic joint book reading situations and analyzed their multimodal communication and its relation to the children?s l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Multimodal communication between mother and child in a joint book reading situation explains 55% of the variation in the children's later vocabulary (Grimminger & Rohlfing, 2019). In a persistence study of 29 18-month-old infants, Lucca et al (2019) found that parental persistent verbal encouragement during joint book reading also significantly predicted the child's future persistence qualities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimodal communication between mother and child in a joint book reading situation explains 55% of the variation in the children's later vocabulary (Grimminger & Rohlfing, 2019). In a persistence study of 29 18-month-old infants, Lucca et al (2019) found that parental persistent verbal encouragement during joint book reading also significantly predicted the child's future persistence qualities.…”
Section: Introductionmentioning
confidence: 99%
“…Mother-child joint book reading is the process of a mother and child reading a book together. Many studies have shown that parent-child joint book reading is a very important parent-child interaction activity that not only promotes the reading development of preschool children as well as influences future academic achievement, but also promotes the development of the child's future personality qualities (Bus et al, 1995;Grimminger & Rohlfing, 2019;Lucca et al, 2019;Raikes et al, 2006). Bus et al (1995) Studies have shown that joint book reading is associated with children's language skills, new literacy rates, and reading achievement, and further research has shown that mother-child reading significantly predicts children's later language and cognitive abilities (Raikes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%